Restaurant Accounting System Studies in Indonesia 2021-2022: A Systematic Literature Review - Nelcie Mussa; Yuliana Yuliana; Ika Ismiyar; Effendi Tjahjadi; Agus Munandar (Yayasan Ilomata, 2023)
The purpose of this study is to determine whether the design of an accounting system in a restaurant or franchise business can provide benefits in realizing the creation of accounting reporting that has a positive impact on management. In this study, the application of accounting system design using accounting information system applications was taken from the results of research conducted by previous researchers on restaurants and franchise businesses. The study was conducted based on the literature review of the ten previous studies by making a summary of the results and conclusions. Some of the criteria used in selecting articles to be material in this study are as follows: the method used, trends and topics in related research, factors that influence financial reporting and the next best method used in writing financial reports.The design of an accounting information system using a PHP program and a MySQL database can help companies make financial accounting reports which include the calculation of profit and loss from restaurant companies. PHP applications and MySQL databases used by restaurant companies must comply with applicable accounting standards. Technical competence of employees needs to be given support from the top management of the company to receive special training in the use of financial accounting programs, so that the performance of accounting information systems can be measured for success. The involvement of users of the financial accounting information system program in the company has a positive impact on the performance of the financial accounting system.